Building Strategies for Porcine Cancer Models - Lawrence B. Schook (Frontiers Research Topics, 2018)
The eBook "Building Strategies for Porcine Cancer Models" presents a series of articles demonstrating the state-of-the-art developments in pig models for cancer research. Renowned researchers dedicated to the reproduction, genomic and biological engineering of the pig model for biomedicine contribute to this special research area. Although advances in these areas are occurring at surprising speeds, they are still far from realizing all the potential benefits that this biological model could provide to science. The current biomedical models may limit the frontier of knowledge in the cancer research.